The Pattern of Spending Money on Male and Female Students - Lilly Anggrayni; Sjamsuddin A.K. Antuli; Chadijah Haris; Salsabilah Nur Angraini Taduengo (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2023)
Over 65 Economic students completed the questionnaire on their source of personal income, saving, and spending. The particular attention was the income of the students who are doing part time job and who are not. The respondents also ansewered the various questions about spending money. Over 65% of economic students still depend on their parents on the financial matter and about 10% of students who had independent life. The Purpose of the study was to know the pattern of spending money on male and female of economic students. The Statistic descriptive had been used to test the data which is collected by using google form. This study found that the economic students still had lack of knowledge and skill about financial Literacy.